Utility of lytic bacteriophage in the treatment of multidrug-resistant Pseudomonas aeruginosa septicemia in mice - Vinodkumar C; Kalsurmath Suneeta; Neelagund Y (Wolters Kluwer Medknow Publications, 2008)
Drug resistance is the major cause of increase in morbidity and mortality in neonates. One thousand six hundred forty-seven suspected septicemic neonates were subjected for microbiological analysis over a period of 5 years. Forty-two P. aeruginosa were isolated and the antibiogram revealed that 28 P. aeruginosa were resistant to almost all the common drugs used (multidrug-resistant). The emergence of antibiotic-resistant bacterial strains is one of the most critical problems of modern medicine. As a result, a novel and most effective approaches for treating infection caused by multidrug-resistant bacteria are urgently required. In this context, one intriguing approach is to use bacteriophages (viruses that kill bacteria) in the treatment of infection caused by drug-resistant bacteria. In the present study, the utility of lytic bacteriophages to rescue septicemic mice with multidrug-resistant (MDR) P. aeruginosa infection was evaluated. MDR P. aeruginosa was used to induce septicemia in mice by intraperitoneal (i.p.) injection of 10 7 CFU. The resulting bacteremia was fatal within 48 hrs. The phage strain used in this study had lytic activity against a wide range of clinical isolates of MDR P. aeruginosa. A single i.p. injection of 3 x 10 9 PFU of the phage strain, administered 45 min after the bacterial challenge, was sufficient to rescue 100% of the animals. Even when treatment was delayed to the point where all animals were moribund, approximately 50% of them were rescued by a single injection of this phage preparation. The ability of this phage to rescue septicemic mice was demonstrated to be due to the functional capabilities of the phage and not to a nonspecific immune effect. The rescue of septicemic mice could be affected only by phage strains able to grow in vitro on the bacterial host used to infect the animals and when such strains are heat-inactivated, they lose their ability to rescue the infected mice. Multidrug-resistant bacteria have opened a second window for phage therapy. It would seem timely to begin to look afresh at this approach. A scientific methodology can make phage therapy as a stand-alone therapy for infections that are fully resistant to antibiotics.